An Extension of the Blinder-Oaxaca Decomposition Technique to Logit and Probit Models - Robert W. Fairlie (Yale University, Economic Growth Center, 2003)
The Blinder-Oaxaca decomposition technique is widely used to identify and quantify the separate contributions of group differences in measurable characteristics, such as education, experience, marital status, and geographical differences to racial and gender gaps in outcomes. The technique cannot be used directly, however, if the outcome is binary and the coefficients are from a logit or probit model. I describe a relatively simple method of performing a decomposition that uses estimates from a logit or probit model. Expanding on the original application of the technique in Fairlie (1999), I provide a more thorough discussion of how to apply the technique, an analysis of the sensitivity of the decomposition estimates to different parameters, and the calculation of standard errors.
Keywords: C8; J7; 330; Logit; Probit; Decomposition; Race; Gender; Discrimination; Dekompositionsverfahren; Computer; Rasse; Geschlecht; USA; Logit-Modell; Probit-Modell